Democratic Republic of Sao Tome : Fifth Review Under the Extended Credit Facility Arrangement, Request for Waiver of Nonobservance of Performance Criterion and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of Sao Tome. (IMF Staff Country Reports; Country Report ;, 2022)
The COVID-19 pandemic exacerbated long-standing socio-economic vulnerabilities, which were further compounded by persistent energy shortages, flood-related damages at end-2021, and a sharp increase in global fuel and food prices caused by the war in Ukraine. These have put pressure on domestic inflation, aggravated electricity shortages, and disrupted business activities, with negative implications for growth in 2022. Protracted negotiations with labor unions resulted in additional wage supplements for the lowest paid category of civil servants in June 2022. Parliamentary elections are scheduled to be held in September 2022.